ANALISIS PENGGUNAAN METODE MENDONGENG BERBANTU DIORAMA PADA MAPEL IPA KELAS V SDN 01 SUMBERSOKO KECAMATAN SUKOLILO KABUPATEN PATI - Kharisma, Fera Yuni (JGK (Jurnal Guru Kita), 2019)
Abstract: Analysis of the Use of Diorama's Storytelling Method in Class V Science Workshop in SDN 01 Sumbersoko, Sukolilo Subdistrict, Pati Regency. This research was motivated by the lack of interest of students in science lessons. This is because the learning media used are less attractive so that the learning atmosphere is not conducive which can interfere when the learning process takes place. The storytelling method has been carried out by class V teachers so that the fifth grade students in the learning process are not bored and easy to understand which is explained by the teacher so that students 'learning motivation can increase which can increase students' interest in learning towards the Natural Sciences. Based on the results of the research, suggestions that can be conveyed are that in the use of helpful storytelling methods diorama is not only used in class V students, but also students of class I to class VI also use the learning method. So that students are interested in participating in the lesson by not getting bored when in class and can increase student learning motivation. Learning media storytelling method with the help of diorama is an alternative teacher to deliver material during the learning process takes place.Keywords: Storytelling Method, Diorama, ScienceAbstrak: Analisis Penggunaan Metode Mendongeng Berbantu Diorama pada Mapel IPA Kelas V SDN 01 Sumbersoko Kecamatan Sukolilo Kabupaten  Pati. Penelitian ini dilatarbelakangi karena kurang minatnya siswa terhadap pelajaran IPA. Hal tersebut dikarenakan media pembelajaran yang digunakan kurang menarik sehingga suasana belajar tidak kondusif yang dapat mengganggu pada saat proses pembelajaran berlangsung. Metode mendongeng sudah dilaksanakan guru kelas V agar siswa kelas V dalam proses pembelajaran tidak bosan dan mudah memahami yang diterangkan oleh guru sehingga motivasi belajar siswa meningkat yang dapat meningkatkan minat belajar siswa tehadap Mapel IPA. Berdasarkan hasil penelitian saran yang dapat disampaikan adalah supaya dalam penggunaan metode mendongeng berbantu diorama tidak hanya digunakan pada siswa kelas V saja, tetapi siswa  kelas I sampai kelas VI juga supaya menggunakan metode pembelajaran tersebut. Sehingga siswa tertarik mengikuti pelajaran itu dengan tidak bosan pada saat di kelas dan dapat meningkatkan motivasi belajar siswa. Media pembelajaran metode mendongeng dengan berbantu diorama salah satu alternatif guru untuk menyampaikan materi pada saat proses pembelajaran berlangsung.Kata Kunci : Metode Mendongeng, Diodrama, IPA